PEComa in a Young Patient with Known Li-Fraumeni Syndrome. (4th March 2015) - Neofytou, Kyriakos; Famularo, Simone; Khan, Aamir Z.
Abstract : Perivascular epithelioid cells neoplasms (PEComas) constitute a family of rare tumours which have been reported virtually in all anatomic sites. The histological clarification of the malignant potential of these tumours is still problematic despite the proposed risk stratification systems. Li-Fraumeni syndrome (LFS) is caused by a germline mutation in the TP53 tumour suppressor gene. It is a rare but well-characterized cancer predisposition syndrome leading to the development of a variety of different tumour types. To the best of our knowledge, an association between this syndrome and PEComas has not been previously documented. A 24-year-old lady with known LFS presented with two uncertain-in-nature lesions, one within the right part of the liver and one within the upper pole of the right kidney. The patient underwent an uncomplicated open simultaneous right partial nephrectomy and resection of segment 7 of the liver. The morphological and immunohistochemical features of both lesions were of epithelioid angiomyolipoma (PEComa). Although the obvious scenario was that the liver lesion was a metastasis from the renal lesion, the assessment of their malignant potential according to the existing risk stratification systems was rather in favour of two synchronous primary PEComas, pointing out that the histological assessment of malignant potential of PEComas is still problematic.